Book Review: Mindful Medical Practitioners: A Guide for Clinicians and Educators - Tse, Olivia (Canadian Medical Education Journal, 2020)
The authors of Mindful Medical Practitioners: A Guide for Clinicians and Educators, Patricia Lynn Dobkin and Craig Stephen Hassed, experienced teachers of mindfulness, describe in detail how mindfulness is being taught to medical students, residents and practicing professionals in their respective settings. The book provides guidance and addresses potential questions for clinicians and educators who wish to develop and integrate programs to teach mindfulness within their institutions. It is an invaluable resource that is informative, comprehensive and readable.